The chromatic function in Xenopus Laevis - Slome, David (Department of Biological Sciences, 2023)
In few Amphibia is the extent of visible pigmentary effector activity as striking as in the case of the South African clawed toad. Nevertheless, there is no account on record of the phenomena of colour response in this species.